Travel perspectives : a guide to becoming a travel professional - Gorham, Ginger; Rice, Susan (Australia : Thomson Delmar Learning, 2007)
In the recent years, the travel industry has been buffeted by significant international events such as terrorist attacks; the expanding war on terrorism; outbreaks of contagious diseases, such as Bird Flu and SARS; and hurricanes, floods and tsunami. In addition to these issues, travelers have concerns about security in airports, at hotels, on cruise ships, and on trains; travel scams, thieves; pickpockets; and identity theft.
Ch. 1. Your place in travel -- Ch. 2. Technology and the travel professional -- Ch. 3. Travel in the twenty-first century -- Ch. 4. Basic travel geography -- Ch. 5. Travel destinations -- Ch. 6. Air travel basics -- Ch. 7. Planning United States flight itineraries -- Ch. 8. United States airfares and other charges -- Ch. 9. Ticketing and reporting -- Ch. 10. Accommodations -- Ch. 11. Rental cars -- Ch. 12. Traveling by rail.
Includes bibliographical references and index.
Keywords: TRAVEL AGENTS -- VOCATIONAL GUIDANCE